A comment on "The quadratic programming problem with fuzzy relation inequality constraints". (May 2016) - Zhong, Yubin; Zhou, Xue-Gang; Wu, Miao-yu
Highlights: Point out some deficiencies and errors found in the paper which are proposed by Molai. Analysis of the cause of the error. Define a new definition of FRI path of max-product fuzzy relation inequality. Propose some new results. Abstract: This note provides counterexamples to illustrate that Definition 1 and Theorem 2 which are proposed by Molai (2012) are incorrect. We first point out some deficiencies and errors found in the above referenced paper. The incorrect of Theorem 2 is due to the inaccuracy of Definition 1. Then we present a counterexample to illustrate the incorrect of FRI path. At last, we propose a new definition of FRI path of max-product fuzzy relation inequality. Some examples are presented to illustrate that the new definition of FRI path is correct.